Large deformation of an auxetic structure in tension: Experiments and finite element analysis. (15th January 2018) - Zhang, Jianjun; Lu, Guoxing; Wang, Zhihua; Ruan, Dong; Alomarah, Amer; Durandet, Yvonne
Abstract: The present paper reports on the post-yield behaviors of an auxetic structure, honeycomb with representative re-entrant topology. Specimens were made of stainless steel and polymer, respectively. Quasi-static uniaxial tensile tests were conducted in the two principal directions, followed by simulations using the commercial code – ABAQUS 6.11-2. The deformation, tensile stress-strain curves and Poisson's ratio were of interest. A good agreement was observed between the numerical simulations and the experimental results. Subsequently, the effect of cell wall thickness and initial cell angle was studied by means of finite element analysis. An analytical equation was also given for the yield stress of such materials under tension.